The Influence of Professionalism, Work-Discipline, and Trust on the Performance of Nurse Paramedics - Risambessy, Agusthina (Research Horizon, 2023)
Professionals play a vital role in the realm of nurse paramedics and are integral to patient care. This study aims to achieve several objectives: firstly, to analyze and elucidate the impact of professionalism on the performance of nurse paramedics; secondly, to analyze and expound upon the influence of work-discipline on the performance of nurse paramedics; and lastly, to analyze and elaborate on the effect of trust on the performance of nurse paramedics at the Regional General Hospital dr. Ishak Umarella. Employing a saturated sampling technique, a total of 86 employees were included as the sample. The data analysis methodology involves the use of the multiple linear regression method, utilizing SPSS software program version 23. The study's findings provide evidence that professionalism significantly influences the performance of nurse paramedics. Additionally, work-discipline significantly affects the performance of nurse paramedics, while trust also holds a significant impact on their performance within the inpatient Health Centers of the Salahutu District. For future researchers, it is recommended to explore alternative data analysis methods and investigate mediation factors, such as Extra-Role Behavior.